Electric Field Analysis of HDPE/NR Biocomposite Due to Moisture Content Condition - Aziz, Ahmad Farid; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Journal of Electronic Voltage and Application, 2023)
It is critical to develop new insulating materials that can improve the performance of next-generation high-voltage cables used in the construction of future electrical networks. The high electric field reduces solid insulation resistance and causes partial discharge through imperfections in a dielectric, causing the dielectric to age and eventually fail. Moisture is one of the most serious factors the effect the high voltage insulation status of High-Density Polyethylene (HDPE) composites. The main goal of this project is to investigate the electric field intensity of HDPE due to moisture content condition when mixed with 10g, 20g, and 30g of various bio-fillers such as coconut coir fibre, pineapple leaves fibre, and oil palm empty fruit bunch. This can be accomplished by using the Finite Element Method Magnetics (FEMM) 4.2 software to create a two-dimensional (2D) axisymmetric electrostatic model. When compared to unfilled HDPE, the inclusion of bio-filler in HDPE increased the maximum electric field intensity due to moisture content condition. The intensity of the electric field varied with the different percentages of biocomposite loading and their permittivity due to moisture content condition. The results showed, due to moisture content condition, the maximum electric field intensity was significantly lower when HDPE was added with a 10% loading of the oil palm empty fruit bunch (EFB). As a result, EFB bio-filler was the best composition because it tends to improve dielectric properties by having a lower maximum electric field intensity which is 4.214Mv/m due to moisture content condition at the top sphere electrode when compared to other compositions.